Modification model of glued-in rods splice connection using statistical analysis for mengkulang glulam timber - Raja Hussin, Tengku Anita; Hassan, Rohana; Anshari, Buan; Md Nor, Azman; Sapuan, S. M. (Multidisciplinary Digital Publishing Institute, 2023)
The statistical study of the glued-in rod splice connection for Mengkulang glulam timber is presented in this research. This type of connection is used in many applications, such as bridge construction and wide hall, besides becoming increasingly popular due to its cost-effectiveness and ease of installation. Using statistical analysis to evaluate the performance of glued-in rod splice connections is relatively new. Statistical analysis can assess the connection’s performance by examining the glued-in rod splice connection’s strength, stiffness, and durability. Glued-in rods have several advantages over traditional mechanical connections generally used in beam design, such as higher stiffness, more uniform stress distribution, fewer rod corrosion problems and better appearance. Due to this limitation, the standard design for glued-in rods using glulam is the estimated extrapolation for solid timber guidelines. The main objectives of this research were to develop the pull-out model and validate the effectiveness of the model equation for glued-in rods parallel (GRPS0°) and perpendicular (GRPS90°) to the grain directions using a statistical package for the social sciences (SPSS). The variables examined were the number of rods, diameter, length, spacing, the kind of glue utilised, and the number of adhesive layers. In conclusion, the model development clearly shows that most of the parameters achieved the R2 more than 80% accurate for both parallel (GRPS0°) and perpendicular (GRPS90°) to the grain directions.